(untitled) (Hilo Analítico, 2022)
Abstract This research presents the analysis of the perception of gender violence on the part of 4 women from a large city (Bogotá) and a medium-sized town (San Marcos), who are in a couple relationship between the ages of 20 and 27 years old. The objective of the research focuses on the analysis of the perception of gender violence of the participants of the sample. The theoretical framework is based on studies on: male domination, gender violence, intimate partner violence, effects of violence on women, psychological violence and femicide. The methodology is carried out from a qualitative approach, with the open interview instrument, for the analysis the following categories are taken into account: role of the woman in a relationship, perception of gender violence and forms of coping. It is handled from a hermeneutic design. The results of the research suggest that the participants in general are aware of the facts that they should not endure in their relationships and what they should do at the first moment of feeling assaulted and in addition to this, furthermore, although when acts of violence are made up of them, they do not recognize them and accept the violence. But despite this it it is evident that there is empowerment and struggle from the couple relationships against gender violence, without discriminating region. Key words: gender violence, role of women, couple relationship, forms of coping, perception of violence.